2014
DOI: 10.1002/elan.201300547
|View full text |Cite
|
Sign up to set email alerts
|

Application of PEDOT‐CNT Microelectrodes for Neurotransmitter Sensing

Abstract: In this work, composite microelectrodes from poly(3,4‐ethylenedioxythiophene) (PEDOT) and carbon nanotubes (CNT) are characterized as electrochemical sensing material for neurotransmitters. Dopamine can be detected using square wave voltammetry at these microelectrodes. The CNTs improve the sensitivity by a factor of two. In addition, the selectivity towards dopamine in the presence of ascorbic acid and uric acid was examined. While both electrodes, PEDOT and PEDOT‐CNT are able to detect all measured concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…It is reported that DA will undergo subsequent chemical reactions following the electrochemical oxidation . The products of the oligomeric or polymeric reaction are easily absorbed onto the surface of the electrodes and result in a disturbance on the electrochemical oxidation of DA, leading to a lower current density . However, an excellent linear relationship between the peak currents and the DA concentrations can be obtained in the lower DA concentration range from 0.1 to 2 μM (inset of Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that DA will undergo subsequent chemical reactions following the electrochemical oxidation . The products of the oligomeric or polymeric reaction are easily absorbed onto the surface of the electrodes and result in a disturbance on the electrochemical oxidation of DA, leading to a lower current density . However, an excellent linear relationship between the peak currents and the DA concentrations can be obtained in the lower DA concentration range from 0.1 to 2 μM (inset of Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…22, 4685-4692 full papers electrodes and result in a disturbance on the electrochemical oxidation of DA, leading to a lower current density. [ 39 ] However, an excellent linear relationship between the peak currents and the DA concentrations can be obtained in the lower DA concentration range from 0.1 to 2 µM (inset of Figure 7 d). The linear regression equation is: I DA (A/cm 2 ) = 6.1230 × 10 −10 + 1.9399 × 10 −6 C DA (µM) (r 2 = 0.9998).…”
Section: Electrochemical Sensing Performancementioning
confidence: 86%
“…The high capacitance of the material originates from the pseudo-or redox-capacitance of PEDOT (Bard and Faulkner, 2001 ; Gerwig et al, 2012 ). Charge transfer capacitance is then further enhanced by the nanometer scale porosity of the CNT scaffold, that increases the surface area of PEDOT:PSS available to the solution (Gerwig et al, 2012 ; Samba et al, 2014 ). In fact, PEDOT-PSS-CNT is a very promising material for neural interfaces as, with respect to conventional metal electrodes, shows higher conductivity, better electrochemical stability, greater mechanical properties and has shown to perform well during in vivo recordings (Gerwig et al, 2012 ; Castagnola et al, 2013 ; Chen et al, 2013 ; Kozai et al, 2015 ; Samba et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using CNTs in the design of MEAs is that CNTs are chemically inert and stable. Furthermore, CNTs exhibit excellent electrical conductivity and, most importantly, biocompatibility with neurons (Lin et al, 2009 ; Gerwig et al, 2012 ; Musa et al, 2012 ; David-Pur et al, 2014 ; Samba et al, 2014 ). When embedded in polymer film, these CNT electrode arrays provide a flexible device to record activity that can be implanted in the brain.…”
Section: Neuronal and Glial Responses To Nanostructuresmentioning
confidence: 99%